Adverse event reporting in intervention research for young autistic children. (February 2021) - Bottema-Beutel, Kristen; Crowley, Shannon; Sandbank, Micheal; Woynaroski, Tiffany G
Our team examined 150 reports on group-design, non-pharmacological interventions for young autistic children, to determine the prevalence of adverse event reporting. We found that only 11 studies mentioned adverse events; one indicated adverse events occurred, and an additional three indicated adverse effects occurred (i.e. adverse events that could be attributed to the intervention). We also coded reasons for participant withdrawal and found that of the 54 studies that reported reasons for withdrawal, 10 studies reported reasons that could be categorized as adverse events, 8 reported reasons that could be categorized as adverse effects, and an additional 12 studies reported reasons that were too vaguely described to determine adverse event status. We recommend that autism intervention researchers make concerted efforts to monitor, classify, and report adverse events so that practitioners, policy-makers, and families are better equipped to weigh potential benefits of interventions against potential harms. Lay abstract: In this study, we looked at published research on interventions for young autistic children that did not involve administering medication. We were interested in determining how often studies reported on whether adverse events (i.e. physical or psychological distress to the participants) or adverse effects (i.e. adverse events that are thought to be caused by the intervention) had occurred. We found that of the 150 reports we examined, only 11 mentioned adverse events. One of these studies reported adverse events occurred, and three reported that adverse effects occurred. We also reviewed the studies to examine the reasons that were given to explain why any participants dropped out of the intervention (termed "withdrawal"), to determine if any of these reasons could be considered adverse events or adverse effects. Fifty-four studies described reasons for withdrawal, and 10 of these studies had reasons that could be categorized as an adverse event, 8 studies had reasons that could be categorized as an adverse effect, and an additional 12 studies had reasons that were too vaguely described to determine whether they were adverse events or not. We recommend that autism intervention researchers develop more systematic methods of looking for and reporting adverse events and effects, so that professionals and families can be better informed when choosing to enroll their autistic children in interventions.